2019
DOI: 10.1103/physrevlett.123.057203
|View full text |Cite
|
Sign up to set email alerts
|

Effective Spin-Mixing Conductance of Heavy-Metal–Ferromagnet Interfaces

Abstract: The effective spin-mixing conductance ( eff ↑↓ ) of a heavy metal/ferromagnet (HM/FM) interface characterizes the efficiency of the interfacial spin transport. Accurately determining eff ↑↓ is critical to the quantitative understanding of measurements of direct and inverse spin Hall effects. eff ↑↓ is typically ascertained from the inverse dependence of magnetic damping on the FM thickness under the assumption that spin pumping is the dominant mechanism affecting this dependence. Here we report that, this assu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
173
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 52 publications
8
173
0
1
Order By: Relevance
“…In a SOT-MRAM, the spin current generated by the spin Hall effect (SHE) [10][11][12][13] of a heavy metal layer switches the magnetic free layer of a MTJ (see Figure 1a). [1] Recent harmonic response measurements on Au 1−x Pt x /Co bilayers [18,19] have indicated that the Au 0.25 Pt 0.75 alloy can be a particularly compelling spin Hall metal for energy-efficient SOT applications due to the combination of a relatively low resistivity (ρ xx ≈ 80 µΩ cm) with a strong antidamping SOT efficiency (ξ DL j ≈ 0.3-0. [7,[14][15][16][17] SOT-MRAMs based on a spin Hall metal that combines a giant spin Hall ratio (θ SH ) with a relatively low resistivity (ρ xx ) can also have unlimited endurance due to the suppression of Joule heating induced bursting and migration of the write line [2] as well as low values of write impedance that is compatible with superconducting circuits in cryogenic computing systems.…”
Section: Energy-efficient Ultrafast Sot-mrams Based Onmentioning
confidence: 99%
See 4 more Smart Citations
“…In a SOT-MRAM, the spin current generated by the spin Hall effect (SHE) [10][11][12][13] of a heavy metal layer switches the magnetic free layer of a MTJ (see Figure 1a). [1] Recent harmonic response measurements on Au 1−x Pt x /Co bilayers [18,19] have indicated that the Au 0.25 Pt 0.75 alloy can be a particularly compelling spin Hall metal for energy-efficient SOT applications due to the combination of a relatively low resistivity (ρ xx ≈ 80 µΩ cm) with a strong antidamping SOT efficiency (ξ DL j ≈ 0.3-0. [7,[14][15][16][17] SOT-MRAMs based on a spin Hall metal that combines a giant spin Hall ratio (θ SH ) with a relatively low resistivity (ρ xx ) can also have unlimited endurance due to the suppression of Joule heating induced bursting and migration of the write line [2] as well as low values of write impedance that is compatible with superconducting circuits in cryogenic computing systems.…”
Section: Energy-efficient Ultrafast Sot-mrams Based Onmentioning
confidence: 99%
“…[15] Low value of 4πM eff reduces the critical current for antidamping switching. [22,23] All measurements were performed at room temperature. As determined by vibrating sample magnetometry, the saturation magnetization (M s ) of the Fe 0.6 Co 0.2 B 0.2 layers is 1240 emu cm −3 .…”
Section: Energy-efficient Ultrafast Sot-mrams Based Onmentioning
confidence: 99%
See 3 more Smart Citations